2008
DOI: 10.1089/jmf.2007.546
|View full text |Cite
|
Sign up to set email alerts
|

Rosa damascena Decreased Mortality in Adult Drosophila

Abstract: The effects of a rose-flower extract, Rosa damascena, on the mortality rate of Drosophila melanogaster was evaluated in this study. R. damascena is a potent antioxidant that has many therapeutic uses in addition to its perfuming effects. Supplementing Drosophila with this rose extract resulted in a statistically significant decrease in mortality rate in male and female flies. Moreover, the observed anti-aging effects were not associated with common confounds of anti-aging properties, such as a decrease in fecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 23 publications
2
30
0
Order By: Relevance
“…Most pharmacological, gerontological, and demographic investigations require an abundance of flies for individual treatment. [10][11][12][13][14] Thus, the maintenance of a bulk population of flies in such studies is of prime significance.…”
Section: Introductionmentioning
confidence: 99%
“…Most pharmacological, gerontological, and demographic investigations require an abundance of flies for individual treatment. [10][11][12][13][14] Thus, the maintenance of a bulk population of flies in such studies is of prime significance.…”
Section: Introductionmentioning
confidence: 99%
“…dulce (Apiaceae), it was reported that α-pinene had a protective effect on hepatotoxicity caused by carbontetrachlorore (Ozbek et al, 2006). Jafari et al (2008) found that the extract obtained from Rosa damascena Mill. (Rosaceae) reduced mortality in the adult Drosophila melanogaster.…”
Section: Discussionmentioning
confidence: 99%
“…Many plants are the source of natural antioxidants [6]. The effect of Rosa damascene and Rhodiola on lifespan and other fitness parameters has been studied in D. melanogaster [7]. The anti-ageing activity of blueberry was reported in D. melanogaster through life span experiments [8].…”
Section: * Corresponding Authormentioning
confidence: 99%